دورة ادارة العلاقات العامة في تحقيق الامن المعلوماتي بالمؤسسة - حورية زغودي; فاطمة الزهراء صحراء; د/ فاطمة الزهراء عزيزي (جامعة عمار ثليجي بالاغواط, 2025)
ملخص الدراسة: تتناول هذه الدراسة الدور الحيوي الذي تطلع به إدارة العلاقات العامة في تحقيق الامن المعلوماتي داخل المؤسسات في ظل التحديات المتزايدة المرتبطة بالتحول الرقمي والتهديدات السيبرانية. تهدف هذه الدراسة الى التعرف على دور ادارة العلاقات العامة في تحقيق الامن المعلوماتي بالمؤسسة ،كما اعتمدنا على المنهج الوصفي وبوجه الخصوص منهج المسح بالعينة لأن الدراسات الوصفية عادة ما تعتمد على هاذا المنهج ، كما اعتمدنا ايضا في هذه الدراسة على العينة العشوائية والتي تعرف عادة عبى أنها "العينة التي تتكون من وحدات معينة اعتقادا على أنها تمثل المجتمع الأصلي ،وكانت الدراسة الميدانية على عينة من موظفي مؤسسة اتصالات الجزائر -بالأغواط-. والتي من خلالها توصلنا إلى النتائج التالية :  يمكن لإدارة العلاقات العامة ان تزيد من وعي الموظفين والجمهور بأهمية الأمن المعلوماتي .  يمكن لإدارة العلاقات العامة ان تستخدم تكنولوجيا الحديثة لتعزيز الأمن المعلوماتي .  يمكن لإدارة العلاقات العامة أن تبني ثقة العملاء والجمهور في إجراءات الامن المعلوماتي. Abstract: This study investigates the pivotal role of public relations management in ensuring information security within institutions, especially in light of the growing challenges posed by digital transformation and cyber threats. The main objective is to understand how public relations departments contribute to the protection of institutional data and information systems. The research adopts a descriptive methodology, with a particular emphasis on the sample survey method, as it is widely used in descriptive studies. A random sampling technique was employed—defined as the selection of specific units believed to represent the broader population. The empirical study was conducted on a sample of employees at Algérie Télécom – Laghouat. The findings revealed the following: 1. Public relations management can significantly enhance employees’ and the public’s awareness of the importance of information security. 2. Public relations departments can utilize modern technologies to support and strengthen information security measures. 3. Public relations efforts can foster trust among clients and the general public in the institution’s information security protocols
دراسة ميدانية على عينة من موظفي مؤسسة اتصالات الجزائر - الاغواط -